The Difference and Correlation of Seasonal Enhancement Time of Surface Sensible Heat between the Qinghai-Xizang Plateau and the Arid Region of Northwest China - Rui WANG; Dongliang LI; Hui WANG; Guoyang LU; Liwei LIU; Pengcheng HUANG (Gaoyuan qixiang)
The climatic characteristics of surface sensible heat over the Qinghai-Xizang Plateau （QXP）and the arid area of northwest China are analyzed by utilizing the calculated data of daily surface sensible heat fluxes which come from 88 meteorological stations in the arid area of northwest China and 70 conventional meteorological stations in the central and eastern part of the QXP during 1982-2015.The results show that： （1） The time of sensible heat enhancement over the QXP in spring is generally earlier than that in the arid area of northwest China， and in the arid area of northwest China， the abnormal weakening of sensible heat in autumn occurred earlier in where the abnormal sensible heat enhancement happens earlier.（2） The sensible heat over the QXP is a heat source throughout the year， with the strongest in spring， followed by summer.The sensible heat in the arid area of northwest China presents a single peak type， with weak cold source in winter and strongest sensible heat in summer.While the sensible heat over the QXP is weaker （stronger） in the east and stronger （weaker） in the west in spring， the sensible heat over the Tarim Basin and its northeast， southwest Gansu and Ningxia plain is weaker （stronger） in summer.（3） When the sensible heat enhancement time of the QXP is earlier （later） in the northwest and later （earlier） in the southeast， the sensible heat enhancement time in the south of Tarim Basin and the north of Gansu is earlier （later）， while the sensible heat enhancement time in Jungeer Basin is later （earlier）.The results present a further understanding of the temporal and spatial variation of sensible heat fluxes and land-air interaction over the QXP and the arid area of northwest China， as well as provide a theoretical basis for the protection of grassland ecosystem on the QXP and the prediction of east Asian climate.